1993
DOI: 10.1046/j.1523-1739.1993.07020363.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timber Harvesting on Southern Appalachian Salamanders

Abstract: We compared the species richness and abundance of salamanders on six recent clearcuts (< 10 years old) with that of salamanders on 34 mature forest stands (>50 years old) in southern Appalachian forests in western North Carolina, U.S.A. Catches of salamanders from plots in mature forest stands were about five times higher than those on recent clearcuts. Almost all species and major taxonomic groups of salamanders were adversely affected by timber removal. Mean number of species collected per plot was about twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
198
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(214 citation statements)
references
References 19 publications
13
198
3
Order By: Relevance
“…deMaynadier and Hunter [118] found more than a threefold difference in amphibian abundance between control sites and clear-cuts. Salamanders in particular seem to be more sensitive to clear-cutting than other amphibian groups, and plethodontids experience some of the greatest population declines [118,119,121]. Recently harvested riparian forests may pose ecological traps for migrating salamanders, due to exposed conditions that could subject salamanders to heat and desiccation, reducing survival [69,111,119].…”
Section: Timber Harvestmentioning
confidence: 99%
See 2 more Smart Citations
“…deMaynadier and Hunter [118] found more than a threefold difference in amphibian abundance between control sites and clear-cuts. Salamanders in particular seem to be more sensitive to clear-cutting than other amphibian groups, and plethodontids experience some of the greatest population declines [118,119,121]. Recently harvested riparian forests may pose ecological traps for migrating salamanders, due to exposed conditions that could subject salamanders to heat and desiccation, reducing survival [69,111,119].…”
Section: Timber Harvestmentioning
confidence: 99%
“…Recently harvested riparian forests may pose ecological traps for migrating salamanders, due to exposed conditions that could subject salamanders to heat and desiccation, reducing survival [69,111,119]. In southern Appalachian riparian forests, timber harvest can result in reduced leaf litter mass, depth, and moisture, and the elimination of canopy cover can increase soil temperature while decreasing surface soil moisture [111,121]. Timber harvest in Pacific Northwest riparian forests can increase stream temperatures, impacting cold-adapted stream amphibians, and restrict movement [65,122].…”
Section: Timber Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, numerous studies of the effects of forest management practices on amphibian populations have been conducted, primarily on populations of terrestrial salamanders (Bennett et al 1980;Pough et al 1987;Ash 1988;Petranka et al 1993;1994;Chazal and Niewiarowski 1998;DeMaynadier and Hunter 1998;Harpole and Haas 1999;Herbeck and Larsen 1999;Grialou et al 2000;Hanlin et al 2000). Still, little information exists about such potential problems as the effects of fire suppression or prescribed fires (but see Russell et al 1999), plantation forestry including ditching and bedding, or road construction and increased traffic volume on existing roads (Means et al 1996;Gibbs 1998).…”
Section: Population Studies Of Amphibiansmentioning
confidence: 99%
“…Although many studies have shown negative effects of anthropogenic disturbances on woodland salamanders, such as timber harvest and tree canopy removal, (Petranka et al, 1993;Ash and Bruce, 1994;Ash, 1997;Herbeck and Larsen, 1999;Hocking et al, 2013), some research has shown the potential ameliorating effects of retaining coarse woody debris (CWD), which functions as moist refugia (Moseley et al, 2004;Patrick et al, 2006;Rittenhouse et al, 2008;Kluber et al, 2009). At fine spatial scales, woodland salamanders occupy spatially and temporally variable microhabitats such as leaf litter, rocks, and downed wood.…”
mentioning
confidence: 99%